Penerapan Teks Cerita Sejarah Sebagai Media Ajar dalam Upaya Meningkatkan Literasi Peserta Didik Kelas X E 2 SMA Negeri 2 Ciamis - Alghozali, Recka Aulia; Lathifah, Hana; Ratih, Dewi (Universitas Galuh, 2024)
The research aims to explore the application of historical story texts as a teaching medium in an effort to improve student literacy at SMA Negeri 2 Ciamis. The research using the Classroom Action Research method follows the Kemmis and McTaggart (1988) model which is carried out in two cycles, each consisting of planning, action, observation, and reflection. The subject of the study was 34 students in class X E 2. Data was collected through observations, interviews, and literacy tests before and after the implementation of teaching media. The results of the study show that the use of historical story texts can increase students' literacy and understanding of historical materials, as well as improve social-emotional skills, critical thinking, analytical, and empathy. This can be seen from the increase in the average student literacy score from 74% in the pre-action to 91% in the second cycle. In addition, learning activities showed a significant increase, with active participation in class discussions and group assignments. Literacy includes pre-reading, reading, and post-reading activities, which are applied through group discussions and analysis of the story texts of the novels